The Role of Aspartate Aminotransferase to Platelet Ratio Index as a Non-Invasive Predictor of Variceal Etiology of Upper Gastrointestinal Bleeding - Shrestha, Ashish; Sharma, Pasanda; Lama, Anjila; Gurung, Ram Bahadur (Journal of Lumbini Medical College, 2020)
Introduction: Non-invasive strategies to predict variceal from non-variceal bleeding will be highly beneficialfor preemptive management of Upper Gastrointestinal Bleeding (UGIB). This study aimed to assess the roleof aspartate aminotransferase (AST) to platelet ratio index (APRI) as a non-invasive predictor of varicealetiology of UGIB. Methods: This was a retrospective descriptive study conducted at Endoscopy Departmentof Dhulikhel Hospital between January 2017 and December 2019 in patients presenting with acute UGIB.We assessed the diagnostic utility of the APRI score relative to other objective measures by Area Under theReceiver Operating Characteristic (AUROC) curve analysis. Results: A total of 158 patients with historyof UGIB were included in the study. There were total 123 males (77.8%) and the mean age of the patientswas 50.3Â±16.1 years. The APRI score performed well in predicting a variceal etiology of acute UGIB, withAUROC 0.9. When APRI was used at cut-off of 1.3, it had a sensitivity of 84.1% and specificity of 76.8%,a positive predictive value of 70.7% and a negative predictive value of 89.9% while predicting varicealetiology of UGIB at presentation. The relative risk of varices at an APRI cut-off of 1.3 is 17.5 with a p-valueof